Risk behaviors associated with sexually transmitted infections in adolescents. - Emilio Vidal Borrás; Beatriz Hernández González (Universidad de Ciencias Médicas de La Habana, 2017)
Introduction: Sexually transmitted infections constitute a heterogeneous group of diseases of extreme importance for the world public health due to their magnitude, consequence, and repercussion for the patient, the family, and the society. Adolescents are more highly affected by them. Objective: To identify risky behaviors associated to STI in the adolescence. Material and Methods: An analytical case-control study was conducted to evaluate risky behaviors associated to STI in adolescents in California Polyclinic. A semi-structured and anonymous questionnaire was used to attain information, and the results were represented in charts in which significant statistics were calculated. Results: The greatest number studied was the one of 18 and 19 years of age (47.0 %); 50.5 % presented frequent changes in their couples; 48 % maintained unprotected sexual relations; the risk perception of acquiring a STI both in the study and the control group was 23,2% and 40,3%, respectively. Conclusions: Unprotected sexual relations and frequent changes in couples were the risky sexual behaviors related to Sexually Transmitted Infections. Keywords: sexually transmitted infections, adolescents, risky sexual behavior, risk perception, unprotected sex, condom, risk.